LEGAL STUDY ON PERSONAL DATA PROTECTION BASED ON INDONESIAN LEGISLATION - Lestari, Endang; Rasji, Rasji (Sekolah Tinggi Ilmu Hukum Awang Long, 2024)
Personal data protection is an effort to protect individual privacy rights, which includes the need to protect a person's privacy as well as the protection of their personal data. The type of research in this study is normative juridical, which focuses on the review of positive legal norms.To find out about the protection of personal data regulated in Indonesian Legislation and to find out the obstacles to personal data protection in law and their solutions. In Indonesia, Personal Data Protection has been regulated in Law Number 27 of 2022 concerning Personal Data Protection, Law Number 11 of 2008 concerning Electronic Information and Transactions, and the Regulation of the Minister of Communication and Information of the Republic of Indonesia Number 20 of 2016 concerning Protection of Personal Data on Electronic Systems, and has obstacles in the application of this Law such as the overlap of the old law with the new one, and preventing a legal expert from adopting which Law.In the current technological era, the significance of addressing security factors in the processing of personal data using various technologies has become increasingly critical. While electronic systems have enhanced data security, it is undeniable that the risk of data theft by irresponsible parties still exists. Therefore, regulations or laws are necessary to provide protection for personal data.